The Degree of Independence in European Goods Markets: An I(2) Analysis of German and Norwegian Trade Data - Roger Hammersland (Norges Bank, 2004)
It is almost common knowledge that foreign trade in Europe is characterized by an acceptance of prices set by the world market. Coupled with a constant profit share in domestic sectors this makes European exports vulnerable to vagaries of international demand and prices as well as to crowding out in the wake of shocks to supply. These circumstances have been used to legitimate special measures geared towards shielding the sector from adverse shocks and general preferential treatment in the past. In fact econometric evidence is not totally at odds with this view. However, neither exports in a large European economy like Germany nor in a small open one, like Norway, are characterized by price taking behavior. On the contrary, both nations show strong evidence of monopolistic power in the process governing external prices, implying that supply shocks to a large extent can be passed on to prices. On the other hand exports seem to be heavily subject to the vicissitudes of international trade, a feature compatible with exports determined by demand ex post for prices fixed ex ante.
hdl:11250/2498536
Keywords: C32; F12; F14; 330; polynomial cointegration; higher order non-stationarity monopolistic competition; exports